2002
DOI: 10.1046/j.1365-2141.2002.03544.x
|View full text |Cite
|
Sign up to set email alerts
|

A Leu7Pro mutation in the signal peptide of platelet glycoprotein (GP)IX in a case of Bernard–Soulier syndrome abolishes surface expression of the GPIb–V–IX complex

Abstract: Summary. This paper describes the molecular defect of the second case of Bernard–Soulier syndrome, initially reported in 1957. Analysis of the patient's platelets by flow cytometry and Western blotting failed to detect surface expression of any of the four subunits of the glycoprotein (GP)Ib–V–IX complex and revealed small amounts of intracellular GPIbα, GPIbβ and GPV but no GPIX. DNA sequencing revealed a novel missense mutation in the GPIX gene which replaced Leu (CTG) by Pro (CCG) at position 7 of the signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…The mutation of alanine to proline does not affect the net charge or hydrophobicity of the ␣-helix but presumably disturbs the secondary structure as a result of its helix-breaking properties, thus leading to compromised interaction with the signal recognition protein and abnormal insertion into the endoplasmic reticulum membrane (11). Similar proline mutations in signal sequences have been described in specific diseases (12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 79%
“…The mutation of alanine to proline does not affect the net charge or hydrophobicity of the ␣-helix but presumably disturbs the secondary structure as a result of its helix-breaking properties, thus leading to compromised interaction with the signal recognition protein and abnormal insertion into the endoplasmic reticulum membrane (11). Similar proline mutations in signal sequences have been described in specific diseases (12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 79%
“…It has been suggested that GPIX gene mutations affecting cysteine residues [13,14,21] prevent the formation of intramolecular disulfide-loop structures that are critical for the interaction of the polypeptide with the GPIbb subunit. A mutation involving the GPIX signal peptide was recently shown to drastically affect the biosynthesis of both GPIba and GPIX in affected platelets [23]. While it is not clear how point mutations in the GPIX gene not affecting cysteine residues give rise to the BSS phenotype, it has been postulated that these alter the configuration of the GPIX subunit, thus preventing its normal interaction with other constituents of the complex.…”
Section: Discussionmentioning
confidence: 99%
“…The perfect Kozak sequence consists of gccRccAUGG with AUG as start codon, Sandrock/Knöfler/Greinacher/Fürll/Gerisch/ Schuler/Gehrisch/Busse/Zieger sis of patient's platelets revealed GPIX deficiency by using a GPIX antibody. Within the N-terminal part of GPIX, two different single amino acid substitutions were described causing BSS, one in the signal peptide [21] and one at amino acid 8 [22], both leading to the absence of the GPIb/IX/V complex at the platelet surface. We conclude that the GPIX deletion in the described patient prevents proper formation of the GPIb/ IX/V complex.…”
Section: Analyses Of the Platelet Gpib/ix/v Receptor And Von Willebramentioning
confidence: 99%